Age Estimation Using the Tooth Coronal Index on Mandibular First Premolars on Digital Panoramic Radiographs in an Indian Population - Sneha Sharma; Freny Karjodkar; Kaustubh Sansare; Archana Mehra; Ankit Sharma; Mohd Saalim (Frontiers in Dentistry, 2023)
Objectives: Age estimation is a crucial aspect of forensic odontology, and the Tooth Coronal Index (TCI) has been widely used for forensic purposes in determining age. The aim of this research was to evaluate the effectiveness of TCI in age estimation.